2020
DOI: 10.1111/jdv.16268
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of keratinocyte carcinoma in elderly patients – a review of the current literature

Abstract: A large percentage of the patients with keratinocyte carcinoma (KC, formerly known as non‐melanoma skin cancer) is of advanced age and often too frail for standard therapies. However, no specific treatment recommendations are given for this population. This review aimed to give an overview of the current literature on the best practice for the treatment of elderly patients with KC. A literature search was performed in MEDLINE, using ‘keratinocyte carcinoma’, ‘elderly’, ‘treatment’ and various synonyms. Case re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 83 publications
3
22
1
Order By: Relevance
“…Moreover, despite the fact that MMS is more labor intensive and time consuming than CE, 12 multivariable analyses showed no significant difference in the treatment burden or incidence of complications after MMS when compared with those after CE. Although the results with respect to complications are comparable with those reported in previous studies, 12,22,24,25 the literature on BCC treatment burden is sparse. 21 The results of this study appear consistent with those from available studies reporting that older adults frequently consider the surgical BCC treatment experience as satisfactory.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, despite the fact that MMS is more labor intensive and time consuming than CE, 12 multivariable analyses showed no significant difference in the treatment burden or incidence of complications after MMS when compared with those after CE. Although the results with respect to complications are comparable with those reported in previous studies, 12,22,24,25 the literature on BCC treatment burden is sparse. 21 The results of this study appear consistent with those from available studies reporting that older adults frequently consider the surgical BCC treatment experience as satisfactory.…”
Section: Discussionsupporting
confidence: 81%
“…It seems essential to include treatment burden and its predictors in BCC management to improve time to benefit estimation in older adults. 21,22 Especially in frail older adults with a decreased functional reserve, hospital visits, surgical procedures, and postoperative care can be overwhelming and cause substantial distress. 6,23 Remarkably, older adults included in this study experienced a low overall treatment burden (median VAS score of 8.6; IQR, 7.3-9.4) and overall mortality (6.5%); frailty-related patient characteristics were important predictors of higher treatment Overall, the results of this study showed no reason to assume that the surgical treatment of BCC in the head and neck area is too burdensome only for *At the time of treatment, the maximum age of the included patients was 95 years in both treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, every added year of age increased the possibility of selecting a nonsurgical treatment by 4%. The latter finding contradicts with literature data suggesting that surgical treatment is well tolerated in elderly patients with a similar complication and cure rate as in younger patients 29 . However, it can be explained by the fact that the most important benefit of surgery over non surgical treatments of BCC is the lower long‐term recurrence rate, which renders the age as an important factor to be taken into account for treatment selection 30 .…”
Section: Discussionmentioning
confidence: 70%
“…contradicts with literature data suggesting that surgical treatment is well tolerated in elderly patients with a similar complication and cure rate as in younger patients. 29 However, it can be explained by the fact that the most important benefit of surgery over non surgical treatments of BCC is the lower long-term recurrence rate, which renders the age as an important factor to be taken into account for treatment selection. 30 Interestingly, the location and the diameter of the tumor did not appear to affect the selection on a nonsurgical treatment with the exception of vismodegib, which appeared to be selected on the basis of an increased tumor size.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the development of KC is more prevalent in elderly patients with a median age diagnosis of 70 years and older [ 85 ]. There are several factors that potentially contribute to the frequent occurrence of KC in the elderly, namely prolonged exposure to solar UV radiation and repair mechanisms of the cell that are not functioning at optimum levels [ 86 ].…”
Section: Risk Factors Associated With the Development Of Kcmentioning
confidence: 99%